A study of the association of lipid ratios with thyroid dysfunction in a tertiary medical college in Eastern India - Chaudhuri, Sayani; Arnab Chowdhury; Sayak Biswas (Asian Journal of Medical Sciences, 2024)
Background: Thyroid hormones play a crucial role in major metabolic pathways in the body and dyslipidemia is a major metabolic abnormality seen in thyroid disorders. Cardiovascular diseases (CVDs) are now emerging as the leading cause of morbidity and mortality worldwide and the most important risk factor for CVDs is dyslipidemia. The lipid ratios that have a positive association with CVD risk are atherogenic index of plasma (AIP), Castelli’s risk index (CRI)-I and II, and atherogenic coefficient (AC). Clinically, both an excess and deficiency of thyroid hormones can exacerbate or induce CVDs and lipid ratio can be used as an inexpensive marker for predicting CVD risk. Aims and Objectives: This study aims to evaluate the lipid ratios (AIP, CRI-I, CRI-II, AC) in patients with thyroid dysfunction and compare the results with lipid ratios in euthyroid individuals. This study also aims to find any correlation, if exists, between lipid ratios and serum thyroid-stimulating hormone (TSH) levels in thyroid dysfunction. Materials and Methods: The serum TSH and lipid profile were evaluated in fifty euthyroid, fifty hypothyroid, fifty subclinical hypothyroid, and fifty hyperthyroid patients. The lipid ratios (AIP, CRI-I, CRI-II, AC) were calculated from the lipid profile. Results: The mean lipid ratios were higher in hypothyroid, followed by subclinical hypothyroid cases when compared to euthyroid controls and hyperthyroid patients. A positive correlation was observed between the TSH and lipid ratios in euthyroid, hypothyroid, and subclinical hypothyroid subjects. There was no significant correlation between TSH and lipid ratios in hyperthyroid patients. Conclusion: This study demonstrates that the evaluation of lipid ratios along with TSH can provide an effective screening tool to assess the cardiovascular risk in patients with subclinical and overt hypothyroidism, especially in the absence of imaging techniques in resource-limited centers.